Perioperative outcomes and hospitalization costs of radical vs. conservative surgery for hepatic cystic echinococcosis: A retrospective study. - Honggang Shi; Kahaer Tuerxun; Aizizaimu Yusupu; Zainuer Yusupu; Qilin Xu; Yibin Jia; Musitaba Maimaitireyimu; Tuerhongaji Maimaitiaili; Muzaipaer Muhetajiang; Jiaxin Lin; Chengmin Ma; Xiaofeng Li; et al. (Public Library of Science (PLoS), 2024)
Background Surgical intervention is a crucial treatment for hepatic cystic echinococcosis. However, the choice between radical and conservative surgery remains controversial. This study aimed to compare the perioperative outcomes and hospitalization costs between radical and conservative surgery for hepatic cystic echinococcosis. Method A retrospective cohort study was conducted on patients undergoing surgical treatment at the First People's Hospital of Kashi Prefecture from July 1, 2012, to October 1, 2023. Propensity score-matching analysis was utilized to mitigate patient selection bias between the two surgical groups. Result Of the 434 patients included, 324 underwent conservative surgery and 110 underwent radical surgery. After propensity score-matching, 182 conservative surgery and 102 radical surgery patients were compared. Radical surgery patients experienced longer operative time, higher intraoperative blood loss, increased blood transfusion, and higher costs compared to conservative surgery patients. However, no differences were observed in short-term outcomes, including overall morbidity, death, bile leak, effusion, pulmonary infection, incision infection, intestinal obstruction, ICU stay, abdominal drainage time, and postoperative hospital stays. Conclusion This study suggests that radical surgery is associated with greater surgical complexity and higher hospitalization costs, while it doesn't offer a significant short-term advantage. Conservative surgery may be a viable option in resource-limited settings or for patients unsuitable for complex procedures. Further research with long-term follow-up is needed to determine the optimal approach.